Development and characterization of a high quality plum tomato essence. (30th November 2018) - Zhu, Yaozhou; Klee, Harry J.; Sarnoski, Paul J.
Highlights: The volatile profile of a tomato essence is described and quantified. The essence contained an extensively higher amount of fruity-related volatiles than high-quality fresh tomato juice. Tomato essence may be able to replace the volatile compounds lost during thermal processing. This is the first known report of the creation of a tomato essence created from a high quality plum tomato variety. Abstract: A tomato essence was developed for potential flavor enhancement of juices and other tomato products. The changes in the flavor profile that occur during tomato processing in plum tomatoes were characterized and compared using purge and trap gas chromatography-mass spectrometry (PT-GC–MS). The pilot tomato juices mostly suffered losses in green and fruity note-related compounds. Of the four essence fractions produced, Fractions 1 and 2 were most complementary to the undesirable flavor changes encountered during thermal processing. Fraction 1 was characterized as a "green tomato note", with substantially higher amounts of 2-isobutylthiazole, α-citral, hexanal, 3-hexen-1-ol, and 6-methyl-5-hepten-2-one; Fraction 2 was described as a "fruity tomato note" with relatively percentage change of compounds; and Fractions 3 and 4 were described as "cooked tomato note" and "faint tomato note", respectively. These results demonstrate the feasibility of adding tomato essence to impart desirable flavor attributes to processed tomato products.